2023
DOI: 10.9734/aprj/2023/v11i2208
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mbeya Based Organic Fertilizer on Maize Yield and Yield Components in Malawi

Abstract: The recent boom in organic business in the name of Mbeya manure fertilizer has taken shape in commercialisation without government approval as several implications were at stake. Laboratory and field experiments were, therefore, conducted to ascertain the quality of the products with and without modifications. The original products, as proclaimed by suppliers, were evaluated against the control treatment of inorganic fertilizer and the modified products by the inclusion of specific microorganisms in solubilisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Additionally, a study conducted by Kumari (2017), found that the application of N and P fertilizers significantly increased the biomass of harvested plants. Similarly, researchers conducting related studies on maize have also discovered that increased levels of N, P, K, and Zn result in higher grain yield, plant biomass, and seed weight (Bashan et al, 2013;Mwafulirwa, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study conducted by Kumari (2017), found that the application of N and P fertilizers significantly increased the biomass of harvested plants. Similarly, researchers conducting related studies on maize have also discovered that increased levels of N, P, K, and Zn result in higher grain yield, plant biomass, and seed weight (Bashan et al, 2013;Mwafulirwa, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…These crops are crucial for generating edible oils, which are essential components of the Indian diet and various industrial processes. Mustard plays a crucial role in the Indian diet, offering both culinary variety and nutritional benefits [2][3][4]. Mustard seeds are essential in many regional dishes, often fried in oil to enhance the flavor of curries, pickles, and chutneys.…”
Section: Introductionmentioning
confidence: 99%